The possibility of the occurrence of prophets' miracles in terms of revelation and reason - Alwan, Saad Ahmed (Journal of Tikrit University for Humanities, 2023)
This study aimed to identify the nature of miracles and their importance to prophecy, to identify the difference between miracle and magic, and to identify the possibility of a miracle occurring in terms of revelation and reason. The study reached several results including: Miracles are evidence of the sincerity of the messengers and prophets - peace be upon them -. The real performer of the miracle is Almighty Allah and He supports his prophets with those miracles as if He is saying: My servant was honest in what he reports about me and on my behalf. The miracles denier is the one who denies the explicitness of the Holy Qur’an and the purified Sunnah of the Prophet. Thus, he denies intentionally something inevitable in religion. The miracle is rationally possible, and the Sharia has spoken of it, so it must be believed. The study reached several recommendations, the most important of which are: the necessity of urging more research in these matters due to the human need for prophecy and religion, so that Muslims, especially the youth among them, can know the faith with certainty.